Ancient Egypt : facts at your fingertips. (New York : DK Pub., 2019)
Profiles pharaohs, gods, and ancient objects from archeological excavations.
Includes index.
Keywords: Egypt -- Antiquities -- Juvenile literature; Egypt -- Civilization -- To 332 B.C -- Juvenile literature